Impact of gibberellic acid on seedling growth and enzymatic activity in bean cultivars with contrasting seed vigor - Yasmin Pincegher Siega; Cileide Maria Medeiros Coelho; Mariana Bertoncini Peixoto da Silva; Matheus Rodrigues Magalhães Albuquerque; Matheus Santin Padilha; Giselle Camargo Mendes (Acta Scientiarum. Agronomy, 2025)
Soaking seeds in gibberellin acid (GA) can reveal mechanisms controlling seed vigor. GA acts early in germination, stimulating the synthesis of hydrolytic enzymes that break down starch to provide the energy needed for radicle protrusion. This study investigated the effects of gibberellic acid (GA3) on physiology, biochemistry, and molecular components in bean cultivars with different vigor levels. Two cultivars (BAF44, low vigor; and BAF55, high vigor) were soaked in water or 0.035 mM L-1 GA3. The imbibition curve displayed a triphasic pattern; however, exogenous GA3 accelerated root emergence only in cultivar BAF44. GA3 increased root growth only in cultivar BAF44, but increased hypocotyl and epicotyl lengths in both cultivars. GA3 treatment improved seedling length in the low-vigor cultivar, resulting in more vigorous seedlings. This is likely due to increased gene expression and activity of alpha-amylase, leading to greater starch and total soluble sugar reduction in cotyledons, providing more energy for growth points. The initial seed vigor of beans is crucial for how GA3 affects reserve mobilization dynamics.